2010
DOI: 10.3109/08977190903512594
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of IGFBP-1 and -3 correlates with disease activity and differentiates focal segmental glomerulosclerosis and minimal change disease

Abstract: The glomerular microenvironment is influenced by circulating growth factors that are filtered from the blood stream and pass the glomerular filtration barrier. In this study, we wanted to explore the role of IGF-binding proteins (IGFBPs) in two diseases that concern podocytes. We analyzed glomerular expression and urinary excretion of IGFBP-1, -2, and -3 in patients with focal segmental glomerulosclerosis (FSGS) or minimal change disease (MCD). We found that patients with active FSGS excrete high amounts of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…This was achieved by studying ex vivo glomeruli of 6 week‐old wild‐type mice given an IGF‐II analogue [Des(1‐6)IGF‐II; Novozymes] that is unable to bind to, and therefore is not modulated by, the IGFBPs . This is important, as IGFBPs are present locally in the glomerulus , which could prevent native IGF‐II from binding to the IGF‐IR. We then went back to our human podocytes and found that IGF‐II also activated both the PI3K and MAPK pathways in these cells, with kinetics similar to insulin (Figure D, E).…”
Section: Resultsmentioning
confidence: 99%
“…This was achieved by studying ex vivo glomeruli of 6 week‐old wild‐type mice given an IGF‐II analogue [Des(1‐6)IGF‐II; Novozymes] that is unable to bind to, and therefore is not modulated by, the IGFBPs . This is important, as IGFBPs are present locally in the glomerulus , which could prevent native IGF‐II from binding to the IGF‐IR. We then went back to our human podocytes and found that IGF‐II also activated both the PI3K and MAPK pathways in these cells, with kinetics similar to insulin (Figure D, E).…”
Section: Resultsmentioning
confidence: 99%
“…Until now, the relationship between minimal change disease and primary FSGS is still controversial; whether minimal change disease and primary FSGS represent different diseases or a continuum of one disease with different phenotypes is still unknown. There have been many studies focused on differentiation of the two glomerular diseases, and some investigators claimed several biomarkers that might facilitate the differentiation, [13][14][15][16][17][18][19] including proteins expressed on podocytes and molecules excreted into urine, but none of these biomarkers were confirmed reliable. In this study, we found that the plasma suPAR levels, in part, of our patients with primary FSGS were higher than that in patients with minimal change disease and membranous nephropathy, which indicated that the elevation of plasma suPAR might be related to the pathogenesis of primary FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 treatment accelerates recovery in animal models of AKI, but clinical trials had controversial results [ 78 ]. IGFBP-3 and IGFBP-1 levels are increased in patients with FSGS, but not in patients with MCD [ 89 ]. IGFBP-1 levels are also elevated in the kidneys in a mouse model of experimental IgA glomerulonephritis and in serum of patients with IgA glomerulonephritis.…”
Section: Insulin-like Growth Factors (Igf) and Insulin-like Growthmentioning
confidence: 99%